2023
DOI: 10.3390/computation11060111
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Characteristics of Associative Storage Devices in Radio Telemetry Systems with Data Compression

Bulat-Batyr Yesmagambetov,
Akhmetbek Mussabekov,
Nurlybek Alymov
et al.

Abstract: In the radio telemetry systems of spacecraft, various data compression methods are used for data processing. When using any compression methods, the data obtained as a result of compression is formed randomly, and transmission over radio communication channels should be carried out evenly over time. This leads to the need to use special buffer storage devices. In addition, existing spacecraft radio telemetry systems require grouping of compressed data streams by certain characteristics. This leads to the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of particular interest is the formation of output streams of compressed data obtained in accordance with expression (19) and their connection to the communication channel. Some aspects of this problem are covered, for example, in [32]. The results of statistical modeling showed that the method is quite effective.…”
Section: Results Of Computer Modelingmentioning
confidence: 99%
“…Of particular interest is the formation of output streams of compressed data obtained in accordance with expression (19) and their connection to the communication channel. Some aspects of this problem are covered, for example, in [32]. The results of statistical modeling showed that the method is quite effective.…”
Section: Results Of Computer Modelingmentioning
confidence: 99%
“…Of particular interest is the formation of output streams of compressed data obtained in accordance with expression (19) and their connection to the communication channel. Some aspects of this problem are covered, for example, in [27].…”
Section: Discussion and Resultsmentioning
confidence: 99%